Talasemia : sebuah Tinjauan Pustaka - Canis Paloma, I Dewa Ayu Natih (Department of Pharmacy, Bumigora University, 2023)
Thalassemia is a genetic disorder in red blood cells so sufferers must do blood transfusions throughout their lives. Diagnosis is made based on anamnesis, physical examination, and supported by supporting examinations. Management in general is to do a blood transfusion. Management can be different for each individual depending on the condition of the patient. This literature review was made to increase knowledge about thalassemia through literature studies. Study searches were carried out through books and library websites such as PubMed and Google Scholar on related topics. The types of articles selected include review articles, narrative reviews, books, and research results which are publications in Indonesian or English as the main source.